2021
DOI: 10.1038/s41375-021-01147-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of complete lncRNAs transcriptome reveals the functional and clinical impact of lncRNAs in multiple myeloma

Abstract: Multiple myeloma (MM) is an incurable disease, whose clinical heterogeneity makes its management challenging, highlighting the need for biological features to guide improved therapies. Deregulation of specific long non-coding RNAs (lncRNAs) has been shown in MM, nevertheless, the complete lncRNA transcriptome has not yet been elucidated. In this work, we identified 40,511 novel lncRNAs in MM samples. lncRNAs accounted for 82% of the MM transcriptome and were more heterogeneously expressed than coding genes. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…The signi cance of the characteristics of complete lncRNAs transcriptome in MM was also analyzed by Carrasco-Leon et al, 40511 novel lncRNAs have been identi ed in MM samples, accounts for 82% of the MM transcriptional group, which is more heterogeneously expressed than the coding gene. Compared with normal bone marrow plasma cells, a total of 10351 overexpressed and 9535 down-regulated lncRNAs were identi ed in MM patients [33] . However, there were no reports on the differentially expressed lncRNAs and their cis-regulated target mRNAs in healthy adults, newly diagnosed MM, and relapsed MM.…”
Section: Discussionmentioning
confidence: 99%
“…The signi cance of the characteristics of complete lncRNAs transcriptome in MM was also analyzed by Carrasco-Leon et al, 40511 novel lncRNAs have been identi ed in MM samples, accounts for 82% of the MM transcriptional group, which is more heterogeneously expressed than the coding gene. Compared with normal bone marrow plasma cells, a total of 10351 overexpressed and 9535 down-regulated lncRNAs were identi ed in MM patients [33] . However, there were no reports on the differentially expressed lncRNAs and their cis-regulated target mRNAs in healthy adults, newly diagnosed MM, and relapsed MM.…”
Section: Discussionmentioning
confidence: 99%
“…One example of the latter is SMILO (specific myeloma intergenic long noncoding RNA), which, due to loss of DNA methylation, becomes epigenetically activated. The activation of SMILO results in its overexpression and promotes MM cell survival via the changing expression of the genes involved in nucleosome assembly, nonsense-mediated decay, chromatin silencing and cell adhesion [62]. Overall, SMILO overexpression in MM has antiapoptotic and pro-proliferative effects due to the suppression of several interferonstimulated genes (ISGs-ISG15, IFI27 and MX1).…”
Section: Gene-specific Hypermethylationmentioning
confidence: 99%
“…[25] Additionally, studies have revealed how the knockdown or upregulation of certain lncRNAs is also associated with different biological and phenotypic effects in MM cells, such as decrease in cell proliferation or viability, decrease in cellular migration, increase in cellular apoptosis and cell cycle arrest indicating possible roles for lncRNAs in the pathobiology of MM. [26] Further, an increasing number of studies have indicated that the abnormal expression of certain lncRNAs is linked to the overall survival (OS), and the progression free survival (PFS) of patients with myeloma [27] leading to identi cation of long noncoding RNAs as potential novel biomarkers for predicting patient's outcome [28,29] and potential drug targets.…”
Section: Introductionmentioning
confidence: 99%